2020
DOI: 10.1371/journal.pone.0235680
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of kidney allograft survival in the Eurotransplant senior program after changing the allocation criteria in 2010—A single center experience

Abstract: The European Senior Program (ESP) aims to avoid waiting list competition between younger and elderly patients applying for renal transplantation. By listing patients �65 years on a separate waiting list and locally allocating of grafts �65 years exclusively to this cohort, waiting and cold ischemia times are predicted to be shortened, potentially resulting in improved kidney transplantation outcomes. This study compared a historic cohort of renal transplant recipients being simultaneously listed on the general… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In 2010 allocation criteria were modified by listing patients ≥65 years on a separate local waiting list and allocating grafts ≥ 65 years exclusively to older recipients included in the list. Compared to the historical cohort, locally allocated recipients experienced significantly shorter time on dialysis and had better graft survival in the long-term [ 74 ]. The success of the program induced a Consensus Meeting to propose that kidney organs from 65- to 74-year-old donors could also be allocated to 55- to 64-year-old recipients [ 75 ].…”
Section: Risk Factors For Dgfmentioning
confidence: 99%
“…In 2010 allocation criteria were modified by listing patients ≥65 years on a separate local waiting list and allocating grafts ≥ 65 years exclusively to older recipients included in the list. Compared to the historical cohort, locally allocated recipients experienced significantly shorter time on dialysis and had better graft survival in the long-term [ 74 ]. The success of the program induced a Consensus Meeting to propose that kidney organs from 65- to 74-year-old donors could also be allocated to 55- to 64-year-old recipients [ 75 ].…”
Section: Risk Factors For Dgfmentioning
confidence: 99%
“…Effective strategies to facilitate allocation of unwanted kidneys within a timeframe that minimizes discard and that improves logistical considerations in the United States are desperately needed. Implementation of “expedited” or “rescue” allocation of kidneys at risk for discard that were initiated within the United Kingdom in 2012 15 and Eurotransplant in 2006 16,17 have been shown to reduce CIT 18 and stabilize discard rates at comparable outcomes to standard allocation 15,16 . Other opportunities to reduce CIT, besides allocation offer efficiency, are operational, such as reducing the time required for organ assessment (e.g., biopsy standards and access to pathological interpretation), 19 determination of histocompatibility, 20 organ transportation, and transplant center actions (i.e., operating room availability, pre‐transplant dialysis) 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a recent report that a pretransplant malignancy was associated with the graft survival [39]; however, we analyzed the data to determine only the de novo cancer incidence after KT, so we were unable to examine the association between cancer incidence and graft outcome. In addition, thanks to the European Senior Program in Europe, a systematic research about factors related to the prognosis of KT in elderly people was recently reported [40]. However, there is no such program in South Korea for the elderly; therefore, the association between cancer risk and the possibility of kidney transplants being carried out differently depending on age could not be evaluated.…”
Section: Discussionmentioning
confidence: 99%